Innovative design and optimization of the modular high deployment ratio two-dimensional planar antenna mechanism. (August 2022) - Liu, Mingli; Shi, Chuang; Guo, Hongwei; Ma, Xiaofei; Liu, Rongqiang; Hu, Fei
Highlights: The configuration of the two-dimensional deployable planar antenna is innovative. Through kinematic analysis and planning speed, the antenna can be deployed smoothly. Based on the response surface method, the parameters of the mechanism are optimized. The deployment function of the antenna is verified through prototype experiments. Abstract: With the improvement of space-to-earth observation range and observation accuracy, the demand for large deployable antenna mechanism is becoming increasingly urgent. This paper proposes a new configuration that can realize two-dimensional planar deployment and designs a new large-scale two-dimensional deployable planar antenna mechanism. First, four folding schemes are proposed, and the folding scheme with the best comprehensive performance is determined through optimization. The antenna mechanism is designed in detail. The kinematic model of the basic configuration is established to analyze its kinematic characteristics. The antenna can be deployed smoothly by planning the deployment speed. The finite element model of the antenna is then established. The structural parameters of the antenna are optimized, the rigidity of each joint hinge is reasonably configured, and the comprehensive mechanical properties of the antenna are improved. Finally, the principle prototype of the two-dimensional deployable antenna is developed by 3D printing technology. The rationality and feasibility of the folding principle of the antenna are verified by experiments.